One-round key exchange in the standard model. (26th February 2009) - Boyd, Colin; Cliff, Yvonne; Nieto, Juan M. Gonzalez; Paterson, Kenneth G.
We consider one-round key exchange protocols secure in the standard model. The security analysis uses the powerful security model of Canetti and Krawczyk and a natural extension of it to the ID-based setting. It is shown how Key-Encapsulation Mechanisms (KEMs) can be used in a generic way to obtain two different protocol designs with progressively stronger security guarantees. A detailed analysis of the performance of the protocols is included; surprisingly, when instantiated with specific KEM constructions, the resulting protocols are competitive with the best previous schemes that have proofs only in the Random Oracle Model.